Operational Business Planning Using Lean Canvas at PT ESPA: A Thematic Analysis Qualitative Interview Analysis - Dendra nugraha; Shafarani Putri Raissa; Meuthya Kayla Puspita; Najmi Khairunnisa Gunawan; Aura Diva Nadira; Muhammad Fajar Wahyudi Rahman (Universitas Negeri Surabaya, 2026)
PT ESPA experiences recurring operational issues due to the absence of a centralized system, leading to scattered documentation, uneven workflows, and delays in reporting. This study aims to develop an operational business plan that addresses these conditions by applying the Lean Canvas framework supported by qualitative findings. Using a qualitative case study approach, data were gathered through semi-structured interviews with key internal stakeholders across strategic, managerial, and operational levels. The interview data were analyzed using thematic analysis to identify core operational problems and system requirements. The analysis revealed essential themes such as documentation inefficiency, lack of workflow standardization, and the need for an integrated digital platform accessible through multiple devices. These themes were then translated into the nine Lean Canvas components to produce a structured operational model that reflects the company’s real needs. The study concludes that integrating thematic analysis with Lean Canvas provides a practical basis for designing an operational system that improves workflow clarity, accelerates reporting, and strengthens managerial oversight.